(untitled) (Revista INFAD de Psicología. International Journal of Developmental and Educational Psychology., 2014)
The paper presents the experience of team research work aimed at experimental study of attitudes by modern implicit methods. Involvement of students in the creative atmosphere creates the basis for the formation of a creative, competent and responsible psychologist who can then learn how to work in any of the areas of psychology. The results of empirical studies aimed at understanding of ethnic attitudes, hardiness, gambling addiction, alcohol abuse by implicit methods and self-assessment procedures are presented.